On the isomorphism of wreath products of groups - Bodnarchuk, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The well-known Neumann theorem on the isomorphism of standard wreath products is generalized to the wreath products of an arbitrary transitive permutation group and an abstract group.